1995
DOI: 10.1128/aac.39.9.1920
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a novel, plasmid-encoded trimethoprim-resistant dihydrofolate reductase from Staphylococcus haemolyticus MUR313

Abstract: In recent years resistance to the antibacterial agent trimethoprim (Tmp) has become more widespread, and several trimethoprim-resistant (Tmp r ) dihydrofolate reductases (DHFRs) have been described from gramnegative bacteria. In staphylococci, only one Tmp r DHFR has been described, the type S1 DHFR, which is encoded by the dfrA gene found on transposon Tn4003. In order to investigate the coincidence of high-level Tmp resistance and the presence of dfrA, we analyzed the DNAs from various Tmp r staphylococci fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 31 publications
(57 reference statements)
3
34
1
1
Order By: Relevance
“…2). Identities to the known DfrA proteins determined on the basis of a multisequence alignment varied between 20.0 and 37.7%, with the highest levels of identity to the Dfr proteins being found for Bacillus subtilis (37.7%) (7) and Staphylococcus haemolyticus (37.0%) (2). This observation confirmed that DfrA20 is only distantly related to other DfrA proteins.…”
supporting
confidence: 65%
“…2). Identities to the known DfrA proteins determined on the basis of a multisequence alignment varied between 20.0 and 37.7%, with the highest levels of identity to the Dfr proteins being found for Bacillus subtilis (37.7%) (7) and Staphylococcus haemolyticus (37.0%) (2). This observation confirmed that DfrA20 is only distantly related to other DfrA proteins.…”
supporting
confidence: 65%
“…The MIC for TMP of the S. sciuri strain was much higher (1,600 .tg/ml) than those of resistant strains of other CNS species (100-400 ig/m1). The PCR-negative TMP', S. sciuri, may have a resistance determinant different from dfrA, like the dfrD gene possessed by a certain TMP' strain of S. haemolytics (8). When the primers for aacA-aphD were used in PCR, the results were in good correlation with those of the GM sensitivity test: all of the 65 GM' staphylococcal isolates (20 S. aureus, 37 S. epidermidis.…”
supporting
confidence: 54%
“…All of the 37 TMP' S. epidermidis isolates were also PCR positive, while all of the 43 TMP' isolates belonging to other species (27 S. aureus, 8 S. haemolyticus, 5 S. saprophyticus, 2 S. chonii, and 1 S. capitis) were negative. The sequence data reported by Dale et al (7)(8)(9) revealed that the TMP gene of S. aureus, dfrA, has only 5 nucleotides different from the TMP' gene of S. epidermidis, dfrC, and that the P5 and P6 primers for dfrA had only one base mismatch in the P6 primer to the dfrC sequence. Therefore, we assumed that the dfrC gene in TMP' S. epidermidis was amplified with the primers for dfrA by PCR.…”
mentioning
confidence: 99%
“…This eventually affects RNA, DNA, and protein synthesis (11). Resistance to TMP is generally seen as the production of an extra DHFR found on plasmids or other genetic elements (5,9,13). In addition, TMP resistance can result from mutations in the chromosomal gene that result in a higher K i for the drug (1,8,13,17,21), as well as the production of an additional DHFR (7).…”
Section: Discussionmentioning
confidence: 99%